HUBUNGAN JUMLAH LEUKOSIT DENGAN JUMLAH TROMBOSIT PADA PASIEN DEMAM BERDARAH DENGUE (DBD) DI PUSKESMAS PIYUNGAN - Devi, Affari Rahmawati Rima; Rohmah, Astika Nur; Astuti, Tri Dyah (Journal of Indonesian Medical Laboratory and Science, 2024)
Background: Dengue Hemorrhargic Fever (DHF) is an infectious disease caused by the dengue virus. Dengue fever is transmitted by Aedes aegypti and Aedes albopictus mosquitoes. In dengue fever sufferers, when a complete blood test is performed, the most common result is a decrease in the number of leukocytes and the number of platelets. Objectives: This study aims to determine the relationship between the number of leukocytes and platelets in DHF patients at Puskesmas (primary health center) Piyungan. Materials and Methods: The type of research used was analytical observational with a cross sectional research design and the data were collected using total sampling techniques. Data was obtained from medical records with a sample size of 26 patients. The relationship between the number of leukocytes and the number of platelets in dengue fever sufferers was tested using the Spearman’s correlation test.  Results: The result of analysis using the Spearman’s correlation test did not show a significant relationship between the number of leukocytes and the number of platelets in dengue fever patients (p = 0.0774), and the level of relationship was very weak with a positive relationship direction (r = 0.059). Conclusions: there was no significant relationship between the number of leukocytes and the number of platelets in dengue fever patients at Puskesmas Piyungan. A decrease in the number of leukocytes and platelets is a common condition that is often found in dengue fever patients.